The Relationship Between Vertical Jump Height, Arm Muscle Strength, and Arm Muscle Power on Volleyball Smash Results - Aulia Putri Nur Afifah; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Tadulako Journal Sport Sciences And Physical Education, 2026)
Smash performance is a key determinant of scoring effectiveness in college volleyball; however, research that simultaneously examines the combined contribution of lower and upper body physical components in a single regression model at the university athlete level is still limited. This study aims to determine the relationship between jump height, arm muscle strength, and arm muscle explosive power with volleyball smash performance. A quantitative correlational design was used, involving 20 athletes from the Indonesian University of Education Sumedang Campus Student Volleyball Activity Unit, selected using Purposive Sampling technique. The instruments used included a vertical jump test, push-up test, medicine ball throw test, and smash accuracy test. Assumption testing was conducted prior to hypothesis testing, including normality and multicollinearity testing. Data were analyzed using multiple linear regression with SPSS version 26. The results of the study show a significant simultaneous relationship between vertical jump height, arm muscle strength, and arm muscle explosive power with smash performance (F = 222.621; p < 0.001), with an adjusted R² value of 0.972, indicating that 97.2% of the variance in smash performance is collectively explained by these three variables. Partially, arm muscle strength showed a significant relationship with smash performance (p < 0.001), while vertical jump height (p = 0.333) and arm muscle power (p = 0.597) did not show a significant partial relationship. These findings indicate that although physical components collectively contribute to smash performance, arm muscle strength emerges as the most dominant predictor among university-level volleyball athletes.